and, of, the Morphometric Analysis and Proximate Composition of Mole Crabs (Hippidae) from the Tial Coastal Area as a Potential Source of Functional Food - Kaliky, Nunun Ainun Putri Sari; Muhsin, Muhammad Fatratullah; Nurlette, Hartono; Alimudin, Saiful; Abubakar, Shafinaz; Saputra, Anugerah; Achmad, Marlina (Hasanuddin University, 2025)
Sea anthills (Hippidae) are a class of crustaceans that live in tidal zones, with sandy substrates and have the potential to be used as an alternative food source. This research was conducted in November 2023 on Tial beach. Specifically, Tial beach is located east of Ambon Island with fine to medium sandy substrates. This research aims to identify the morphological characteristics of Hippidae, as well as analyze their nutritional content. The data collection method used 5 quadrant transects measuring 2 x 2 m with a distance of 8 m in each quadrant. The results showed that there were Hippidae species found, namely Hippa marmorata with a total of 49 individuals/50m2 with a carapace length ranging from 0.8 cm - 4 cm and a body weight of 0.49 gr - 6.58 gr. Morphometric analysis showed a very strong level of relationship between Hippa marmorata and its growth pattern is positive allometric. The proximate content shows that Hippa marmorata contains protein and fat to support its use as a functional food. These data provide important insights into the morphometric aspects and nutritional value of Hippa marmorata. The results support the use of Hippa marmorata as a low-fat and ecologically potent seafood source.